Search for single b∗-quark production with the ATLAS detector at √s = 7 TeV - Anduaga, Xabier Sebastián (2013)
The results of a search for an excited bottom-quark b∗ in pp collisions at √s = 7 TeV, using 4.7 fb−1 of data collected by the ATLAS detector at the LHC are presented. In the model studied, a single b∗-quark is produced through a chromomagnetic interaction and subsequently decays to a W boson and a top quark. The search is performed in the dilepton and lepton+jets final states, which are combined to set limits on b∗-quark couplings for a range of b∗-quark masses. For a benchmark with unit size chromomagnetic and Standard Model-like electroweak b∗ couplings, b∗ quarks with masses less than 870 GeV are excluded at the 95% credibility level.